Integrated Development Technology of Artificial Intelligence, Big Data and Cloud Computing - Yuemei Ren, Xianju Feng, Lei Li (Forest Chemicals Review, 2021)
In terms of the current development status and future development direction of artificial intelligence, big data and cloud computing, the relationship between the three is inseparable. The essence of the Trinity era is that the development of the future era will focus on the three technologies of artificial intelligence (AI), big data and cloud computing. At the same time, big data has gradually entered people’s vision. After the information revolution, the connection between people’s daily life and data is becoming more and more close. Many enterprises begin to use the mining and analysis of big data to mine the development trend and business model of enterprises, so as to help enterprises obtain higher operation efficiency and stronger competitive advantage. Starting from reality and combined with the author’s work experience, this paper discusses the combination of artificial intelligence, big data and cloud computing.